2019
DOI: 10.1038/s41598-019-42811-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of climate variability, trends, and prediction in the most active parts of the Lake Chad basin, Africa

Abstract: An understanding of climate variability, trends, and prediction for better water resource management and planning in a basin is very important. Since the water resources of the Lake Chad basin (LCB) are highly vulnerable to changing climate, in the present study, a combination of trend analysis methods was used to examine the climate variability and trends for the period of 1951–2015 using observed and Climate Research Unit (CRU) data, and a combination of spectral analysis techniques was used for the predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 70 publications
0
82
0
Order By: Relevance
“…Several studies examined stream flow of Chari-Logone river and rainfall for the last 70 years as main indicators of the Lake Chad fluctuation 31,32 . They suggested that the lake is shrinking due to the decreasing trend observed in both parameters.…”
Section: Lake Chad In Context Of the Climate Changementioning
confidence: 99%
“…Several studies examined stream flow of Chari-Logone river and rainfall for the last 70 years as main indicators of the Lake Chad fluctuation 31,32 . They suggested that the lake is shrinking due to the decreasing trend observed in both parameters.…”
Section: Lake Chad In Context Of the Climate Changementioning
confidence: 99%
“…Our temperature data came from the global gridded dataset (Climate Research Unit (CRU) Time-Series Atmosphere 2020, 11,190 4 of 18 (TS) v4.03) provided by the Climate Research Unit (CRU) at the University of East Anglia, United Kingdom [24]. Given the low spatial and temporal coverage of meteorological stations in Africa, the CRU dataset provides alternative data for climate analysis and has been used in previous studies focused on Nigeria, Africa, and global climate models [25][26][27][28]. In this study, we analyze the trend of rainfall and temperature during the 1961 to 2018 period.…”
Section: Linear Variations In Climate Variables In Nigeria's Agro-ecomentioning
confidence: 99%
“…There is evidence that Spectral analysis of observed and Climate Research Unit (CRU) data, can be used for the prediction of climate variations, e.g. temperature was predicted to increase by 0.65-1.6 °C and precipitation was predicted to decrease by 13-11% in the next two decades (i.e., 2016-2025 and 2026-2035) relative to 1961-1990, in the Lake Chad basin (LCB) [58,59,60,61].…”
Section: Rate Of Climate Variationmentioning
confidence: 99%